Gambaran Adaptasi Fisiologis Bayi Berat Badan Lahir Rendah - Aan Achmad Baharudin; Siti Arifah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to describe the physiological adaptation of low birth weight infants during the first 72 hours of life based on changes in body weight, body temperature, respiratory rate, heart rate, and blood glucose levels. This study used a descriptive approach with a case study design. The results showed that low birth weight infants experienced a gradual physiological adaptation process during the first 72 hours of life. Body temperature increased toward the normal range, respiratory rate and heart rate decreased within physiological limits, indicating stability, while blood glucose levels gradually increased. Initial weight loss remained within normal physiological limits and was followed by a tendency to stabilize on the third day. Low birth weight infants demonstrated increasingly stable physiological adaptation during the first 72 hours of life with adequate neonatal care support. Comprehensive monitoring of physiological parameters is crucial for early detection of complications and optimization of the neonatal adaptation process. The conclusions of this study indicate that low birth weight infants are capable of achieving gradual physiological adaptation during the early neonatal period. Therefore, continuous physiological monitoring and adequate neonatal care are necessary to maintain the stability of the infant's condition and prevent further complications. Keywords: Physiological Adaptation, LBW, Case Study, Neonates, Neonatal Care